7P Marketing Mix in Processed Farm Products by Urban Farming Businesses - Nurdiana; Muhammad Hasan; Miranda; Muhammad Ihsan Said Ahmad; Citra Ayni Kamaruddin; Thamrin Tahir (International Journal of Social Science and Business, 2023)
The increasingly rapid business competition makes every business actor required to continue to innovate in order to develop and maintain their existence. One alternative for business actors to continue to develop and maintain their existence is to apply the 7P marketing mix to their business, especially in urban farming. This study aims to analyze the implementation of the 7P marketing mix on processed agricultural products as well as the supporting and inhibiting factors in implementing the 7P marketing mix. This study uses a qualitative approach with a descriptive method. Data collection techniques used were observation, interviews and FGD, for data analysis used coding techniques. There are 4 informants in this study. The results of this study indicate that in general, the 7P marketing mix for the processed products of the Orchid Women Farmer Group has been implemented. Then for the supporting factors for implementing the 7P marketing mix, namely (1) self-confidence; (2) cooperation; (3) encouragement from agricultural extension workers. The inhibiting factors include (1) lack of literacy; and (2) limited time. All elements of the marketing mix in the processed products of the Orchid Women Farmer Group are considered capable of increasing product sales and making the Orchid Women Farmer Group more exist and known. However, in the implementation process, there are several supporting and inhibiting factors as described in the research results.